Pemanfaatan Limbah Marmer Granit subtitusi Aggregat Kasar serta Limbah Cangkang Kerang dan Cangkang Telur sebagai Subtitusi semen dalam Inovasi Beton yang Ramah Lingkungan - Adhi, Bagas Wahyu; Hidayawan, Ahmad; Setiyanto, Beni; Kurniawan, Andri; Nanda Syahputra, Hanif; Yoga Prastika, Annisa; Ridwan Nurrohim, Rio; Adi Wahyu Nugroho, Satrio; Mayasari, Sri (Universitas Veteran Bangun Nusantara, 2024)
In the current era of technological development, the need for concrete has increased quite significantly in infrastructure development, because concrete itself is the main component of a structure. Exploitation in extracting materials from nature has resulted in a reduction in green land and problems regarding people's awareness of the waste found around them. So there is a need for ideas or innovations to reduce or even end this problem. The use of alternative aggregates can reduce natural damage caused by taking and dredging natural stone. In addition, the use of alternative aggregates can reduce construction costs. The aim of this research is to use Granite Marble Waste as a substitute for Coarse Aggregate and Shell and Egg Shell Waste as a cement substitute in Environmentally Friendly Concrete Innovations. In this research the author used an experimental method. The results of concrete compressive strength testing for normal concrete, the average compressive strength for an estimated age of 28 days is 366.11 kg/cm2, while for Innovation Concrete the average compressive strength at an estimated age of 28 days is 376.54 kg/cm2. The budget plan for conventional concrete is more expensive than innovative concrete. Conventional concrete costs Rp. 2,783,600 while innovation concrete costs Rp. 2,391,500, so it can be concluded that innovative concrete is more economical than conventional concrete with a difference of Rp. 392,100, which means that environmentally friendly innovative concrete is 14.09% cheaper and more economical than conventional concrete.